Features of iron metabolism in patients with HIV infection and pulmonary dissemination in tuberculosis and pneumonia: An exploratory case-control study - Elena A. Borodulina; Elena V. Yakovleva (Russian Open Medical Journal)
Background — Differential diagnosis of pneumonia vs. tuberculosis in patients with HIV infection and pulmonary dissemination syndrome is an important problem in contemporary clinical medicine. The goal of our study was to determine the features of iron metabolism in patients with HIV infection and pulmonary dissemination in tuberculosis and pneumonia. Methods — The case-control study was conducted on 42 cases (patients with tuberculosis, hereinafter referred to as Group 1) and 44 control subjects (patients with pneumonia, hereinafter referred to as Group 2). All of them had HIV infection and syndrome of pulmonary dissemination. For subjects in both groups, we analyzed clinical and social characteristics, along with laboratory data. We also examined hepcidin content, iron concentration, and ferritin level in blood serum, and performed statistical data processing. Findings — There were significant differences between cases and controls in terms of iron metabolism. Hepcidin and hemoglobin levels were statistically significantly higher (p <0·001), whereas iron concentration was lower (p=0·0002) in patients with tuberculosis (cases). Furthermore, there were statistically significant differences between groups in CD4+ T-cell count, viral load, and RBC and WBC counts in complete blood count tests; in duration of complaints prior to hospital admission; and in terms of job stability. Conclusion — The quantitative parameters with the greatest statistical significance of the differences between the groups were iron concentration, hepcidin level, RBC count, WBC count, and CD4+ T-cell count.